2023
DOI: 10.1057/s41599-023-01777-w
|View full text |Cite
|
Sign up to set email alerts
|

Eco-tourism, climate change, and environmental policies: empirical evidence from developing economies

Abstract: Developing ecotourism services is a suitable solution to help developing countries improve the status of sustainable development indicators and protect their environment. The primary purpose of this paper is to find out the effects of green governance variables and carbon dioxide emissions on ecotourism for 40 developing economies from 2010 to 2021. The results confirmed a uni-directional causal relationship between the green governance indicator and the inflation rate of the ecotourism indicator. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…This study showed the significant impacts that tourism has had on the regional economy, which makes it possible to state that tourism is the solution to boost the community's economy. These results are related to those by Shang et al [71], who argue that tourism is an appropriate solution to support developing countries. In addition, Mendoza [72] indicate that tourism is the tool for many families who can obtain income, improve the local image and provide quality service to tourists in the way that Lee and Brahmasrene [73] have outlined, regarding tourism as having a very significant direct impact on economic growth.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study showed the significant impacts that tourism has had on the regional economy, which makes it possible to state that tourism is the solution to boost the community's economy. These results are related to those by Shang et al [71], who argue that tourism is an appropriate solution to support developing countries. In addition, Mendoza [72] indicate that tourism is the tool for many families who can obtain income, improve the local image and provide quality service to tourists in the way that Lee and Brahmasrene [73] have outlined, regarding tourism as having a very significant direct impact on economic growth.…”
Section: Discussionsupporting
confidence: 86%
“…It is essential to recognize that these negative structural breaks not only affected companies and employees directly related to KuélapKuélap but have also had an effect on other local economic sectors. The Regional Chamber of Tourism of Amazonas stated that 50% of the tourism businesses in the region would go bankrupt or withdraw if the closure of Kuélap persisted [71]. The decrease in tourism has an indirect impact on restaurants, hotels, transport companies and other services that depend on the influx of visitors, which generates uncertainty, loss of employment or closure of companies, as was the case of Yucatan in Mexico [37].…”
Section: Discussionmentioning
confidence: 99%
“…The ecotourism sector is a new sector that should be studied by young people, especially for students who have a tendency to start entrepreneurship. The development of the ecotourism sector is also in line with the current world goal of reducing carbon emissions that cause global warming and climate change [4]. This is also supported by the statement that 1/5 of global carbon emissions are attributable to transportation.…”
Section: Introductionmentioning
confidence: 56%
“…When the economy depends on many sectors, fluctuations in a specific sector will not strongly impact the entire economy [33]. Additionally, developing the tourism industry also strengthens local economies [49], boosts exporting [50], enhances national image [37], and creates community stability [51]. Hence, many economists and policymakers believe that boosting tourism development is crucial to combat economic uncertainty.…”
Section: Plos Onementioning
confidence: 99%